Cellular liquid biopsy provides unique chances for disease monitoring, preclinical model generation and therapy adjustment in rare salivary gland cancer patients - Nataša Stojanović Gužvić; Florian Lüke; Steffi Treitschke; Andrea Coluccio; Martin Hoffmann; Giancarlo Feliciello; Adithi Ravikumar Varadarajan; Xin Lu; Kathrin Weidele; Catherine Botteron; Silvia Materna–Reichelt; Felix Keil; et al. (Molecular Oncology, 2025)
While cell‐free liquid biopsy (cfLB) approaches provide simple and inexpensive disease monitoring, cell‐based liquid biopsy (cLB) may enable additional molecular genetic assessment of systemic disease heterogeneity and preclinical model development. We investigated 71 blood samples of 62 patients with various advanced cancer types and subjected enriched circulating tumor cells (CTCs) to organoid culture conditions. CTC‐derived tumoroid models were characterized by DNA/RNA sequencing and immunohistochemistry, as well as functional drug testing. Results were linked to molecular features of primary tumors, metastases, and CTCs; CTC enumeration was linked to disease progression. Of 52 samples with positive CTC counts (≥1) from eight different cancer types, only CTCs from two salivary gland cancer (SGC) patients formed tumoroid cultures (P = 0.0005). Longitudinal CTC enumeration of one SGC patient closely reflected disease progression during treatment and revealed metastatic relapse earlier than clinical imaging. Multiomics analysis and functional in vitro drug testing identified potential resistance mechanisms and drug vulnerabilities. We conclude that cLB might add a functional dimension (to the genetic approaches) in the personalized management of rare, difficult‐to‐treat cancers such as SGC.